Surgical approach about supernumerary teeth - Velásquez Reyes, Víctor (2013)
This clinical case report presents the clinical sequence of the surgical treatment of a supernumerary tooth in transverse position. The surgical treatment (extraction) of the supernumerary teeth are indicated in parts included and which are also within the dental arches; This Odontogenic pathology tends to be found sporadically during the examinations; however, not dealing with it and deal with it can become another dental pathology involving parts adjacent to the lesion. Presents the clinical sequence of the surgical approach to extract a supernumerary tooth in a transverse position.